FACTORS OF SERVICE QUALITY AFFECTING STUDENTS, AS CUSTOMERS, SATISFACTION OF RIDESHARING SERVICES IN VILNIUS, LITHUANIA - Ginavičienė, Jurgita; Sprogytė, Indrė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Nowadays ridesharing has become crucial and extremely popular service. As modern consumers, students have become wiser and more rational, they tend to choose not only high quality transport but also they prefer desirable quality of transportation services. The main aim of this research is to identify the factors of service quality which have impact on customer satisfaction of ridesharing services in Vilnius, Lithuania. This study is an quantitative analysis. 124 students of Vilnius College of Technologies and Design Transport Logistics completed a questionnaire via apklausa.lt about factors which affect their evaluation of ridesharing services. Study participants filled out a questionnaire online and evaluate the importance of the values such as flexibility or speed on a 5-point Likert scale. According to the findings obtained, the opportunity to pay for transport by card, provided safety, reasonable price and comfort are significant factors in order to ensure customer satisfaction of ridesharing service.